Jakarta Evolution Sustainability Innovation With the Presence of the Online Single Submission Risk-Based Approach System, a Solution for Licensing Services in DKI Jakarta Province - Danang Windiatmoko, Agus; Taufik H.; Asropi (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The Indonesian government introduced the Electronically Integrated Business Licensing System, Online Single Submission (OSS), to enhance nationwide business operations. However, the DKI Jakarta Provincial Government concurrently implemented its electronic licensing system, the Jakarta Evolution System, leading to overlapping jurisdiction in license processing. The enactment of the Job Creation Law in 2020 marked a significant shift in licensing regulations, introducing a risk-based business licensing approach determined by the central government. Consequently, the OSS transitioned to the Base Risk Approach (OSS-RBA), mandated for adoption by all Regional Governments. This study addresses two key questions: 1) Examining the mechanism for organizing public services in the business licensing sector based on Online Single Submission in DKI Jakarta, and 2) Identifying obstacles in public services related to Online Single Submission in DKI Jakarta and exploring efforts to overcome these challenges. Employing a qualitative and descriptive research approach, the study highlights that the implementation of Online Single Submission in DKI Jakarta aligns with central government guidelines, consolidating almost all business licenses under OSS authority. Key obstacles include a lack of information and socialization, compounded by legal uncertainties from the central government. Mitigation efforts involve the introduction of innovative OSS-RBA support services, intensified socialization initiatives, and policy adjustments. The study underscores the importance of the DKI Jakarta Provincial Government conducting extensive socialization campaigns for OSS-based business licensing to solidify the legal foundation for risk-based licensing.